EXPLORATION OF POSTMODERNISM IN JEMBER FASHION CARNIVAL IN THE ERA OF TECHNOLOGICAL DISRUPTIONS - Bunga Surawijaya Ningsih; Kartika Bina Kasih; Nurul Hasan; Nova Saha Fasadena (International Conference on Humanity Education and Society (ICHES), 2026)
The ideas that replace the concepts of the contemporary era are known as postmodernism. This research provides a theoretical analysis of postmodern ideas, which are the basis for the emergence of contemporary artistic ideas and are reinforced by the increasing tendency of young Indonesian artists to combine contemporary aesthetic styles with the visual power of traditional culture. As a result, the works created are global in nature but retain their traditional values. The "Algorith" logo in Jember Fashion Carnaval (JFC) 2024 has a postmodern context. This research aims to analyze the "Algorithm" logo in postmodern culture. This research is also expected to provide benefits to provide information about postmodern aesthetic values and meanings contained in the logo. The theories used are postmodern theory and postmodern aesthetics. This research uses literature study method from various books, and writings of thinkers. The result of this research is how the application of the "Algorithm" logo on Jember Fashion Carnaval 2024 in a postmodern context. Postmodern itself can be seen through aesthetic values that have idioms contained in the logo. The strongest postmodern aesthetic idiom related to the above case is pastiche. In addition, there are denotation and connotation meanings in the "Algorithm" logo in Jember Fashion Carnaval 2024. With the final conclusion that the term postmodern aesthetic pastiche can be used to describe the application of postmodern culture. The term "pastiche" combines traditional and contemporary styles. The theme logo for Jember Fashion Carnaval 2024 will be drawn using a logogram perspective with a historical algorithm. In which there is a wayang devile. These two typefaces are used to give a simple or contemporary impression. Modern culture is represented by the colors used in the theme logo that depict "aesthetic partners", allowing creativity to compete internationally in the aesthetic space of the contemporary art world.